Antibacterial profile of Rubus idaeus (Raspberry) : An in vitro study - BANDYOPADHYAY, SAMlRAN; SASMAL, DEVASIS; BORA, MONJIT; GHOSH, MANOl K; SARKAR, MIHIR (The Indian Journal of Animal Sciences, 2011)
The present investigation was carried out to study the antibacterial effect of methanolic extract of Rubus idaeus (R-Me OH) against multi drug resistant isolates (of Haemophilus somnus and Pasteurella (Mannheimia) haemolytica collected from yaks susceptible with MICso and MICso of 12.5 and 20.5 mg/mL. R-MeOH (21mg/mL) viability of both the speci~~rep1ains more than 50%..Â